Biomechanical Stress and Strain Analysis of Mandibular Human Region from Computed Tomography to Custom Implant Development - Gregolin, Rafael Ferreira; Zavaglia, Cecília Amelia De Carvalho; Tokimatsu, Ruís Camargo [UNESP]; Pereira, João A. [UNESP] (Hindawi, 2017)
Currently computational tools are helping and improving the processes and testing procedures in several areas of knowledge. Computed tomography (CT) is a diagnostic tool already consolidated and now beginning to be used as a tool for something even more innovative, creating biomodels. Biomodels are anatomical physical copies of human organs and tissues that are used for diagnosis and surgical planning. The use of tomographic images in the creation of biomodels has been arousing great interest in the medical and bioengineering area. In addition to creating biomodels by computed tomography it is also possible, using this process, to create mathematical models to perform computer simulations and analyses of regions of interest. This paper discusses the creation of a biomodel of the skull-mandibular region of a patient from CT for study and evaluation of efforts in the area of the temporomandibular joint (TMJ) aiming at the design and development of a TMJ custom prosthesis. The evaluation of efforts in the TMJ region due to the forces of mastication was made using the finite element method and the results were corroborated by comparison with mandibular models studied in similar works.